Determination of 19 sulfonamides residues in pork samples by combining QuEChERS with dispersive liquid–liquid microextraction followed by UHPLC–MS/MS. Issue 6 (24th February 2017) - Li, Xiaojing; Yu, Hong; Peng, Rongfei; Gan, Pingsheng
Abstract : A new simple and rapid pretreatment method for simultaneous determination of 19 sulfonamides in pork samples was developed through combining the QuEChERS method with dispersive liquid–liquid microextraction followed by ultra‐high performance liquid chromatography with tandem mass spectrometry. The sample preparation involves extraction/partitioning with QuEChERS method followed by dispersive liquid–liquid microextraction using tetrachloroethane as extractive solvent and the acetonitrile extract as dispersive solvent that obtained by QuEChERS. The enriched tetrachloroethane organic phase by dispersive liquid–liquid microextraction was evaporated, reconstituted with 100 μL acetonitrile/water (1:9 v/v) and injected into an ultra‐high performance liquid chromatography with a mobile phase composed of acetonitrile and 0.1% v/v formic acid under gradient elution and separated using a BHE C18 column. Various parameters affecting the extraction efficiency were investigated. Matrix‐matched calibration curves were established. Good linear relationships were obtained for all analytes in a range of 2.0–100 μg/kg and the limits of detection were 0.04–0.49 μg/kg. Average recoveries at three spiking levels were in the range of 78.3–106.1% with relative standard deviations less than 12.7% ( n = 6). The developed method was successfully applied to determine sulfonamide residues in pork samples.